Transformative Assessment Innovation Based on Multiple Representations in Holistic Learning to Measure Logical and Analytical Thinking - Endang Susilaningsih; Isnaini Putri Salimnah; Sri Nurhayati; Harjono; Lilia Ellany Binti Mohtar; Sharipah Ruzaina Syed Aris (Jurnal Pendidikan IPA Indonesia, 2026)
The focus of chemistry learning across multiple levels of representation is essential for developing students’ conceptual understanding of complex chemical phenomena. However, previous studies have predominantly emphasized the use of multiple representations as instructional strategies, while their application in assessment, particularly in acid-base chemistry, remains limited. Moreover, existing assessment instruments seldom integrate logical and analytical thinking skills simultaneously, and the use of Rasch model analysis for diagnostic assessment in this context is still relatively scarce. To address these gaps, this study aims to develop a Transformative Assessment Innovation Based on Multiple Representations integrated into Holistic Learning to measure students’ logical and analytical thinking skills. This research employed a Research and Development (R&D) approach using the ADDIE model. The participants were second-semester students enrolled in the Basic Analytical Chemistry course at Universitas Negeri Semarang. The assessment instrument was developed as multi-representational items encompassing definitional, macroscopic, submicroscopic, symbolic, and stoichiometric levels, aligned with holistic learning activities. The content validity and reliability of the instrument were analyzed using the Rasch model. The results showed that the developed assessment demonstrated high validity (CVR > 0.80) and excellent reliability (Cronbach’s α > 0.90). Furthermore, the implementation findings indicated that the transformative assessment effectively identified and enhanced students’ logical and analytical thinking skills while providing diagnostic and reflective feedback to support continuous learning. These findings suggest that transformative assessment integrated with multi-representational and holistic learning approaches offers a novel diagnostic framework for strengthening students’ higher-order thinking skills in chemistry education.